ICI 182,780 has agonistic effects and synergizes with estradiol-17 beta in fish liver, but not in testis - Power Deborah M; Teodósio Helena R; Condeça João B; Singh Pratap B; Pinto Patrícia; Canário Adelino (BMC, 2006)
Abstract Background ICI 182,780 (ICI) belongs to a new class of antiestrogens developed to be pure estrogen antagonists and, in addition to its therapeutic use, it has been used to knock-out estrogen and estrogen receptor (ER) actions in several mammalian species. In the present study, the effects and mechanism of action of ICI were investigated in the teleost fish, sea bream (Sparus auratus). Methods Three independent in vivo experiments were performed in which mature male tilapia (Oreochromis mossambicus) or sea bream received intra-peritoneal implants containing estradiol-17 beta (E2), ICI or a combination of both compounds. The effects of E2 and ICI on plasma calcium levels were measured and hepatic and testicular gene expression of the three ER subtypes, ER alpha, ER beta a and ER beta b, and the estrogen-responsive genes, vitellogenin II and choriogenin L, were analyzed by semi-quantitative RT-PCR in sea bream. Results E2 treatment caused an increase in calcium levels in tilapia, while ICI alone had no noticeable effect, as expected. However, pretreatment with ICI synergistically potentiated the effect of E2 on plasma calcium in both species. ICI mimicked some E2 actions in gene expression in sea bream liver upregulating ER alpha, vitellogenin II and choriogenin L, although, unlike E2, it did not downregulate ER beta a and ER beta b. In contrast, no effects of E2 or ICI alone were detected in the expression of ERs in testis, while vitellogenin II and choriogenin L were upregulated by E2 but not ICI. Finally, pretreatment with ICI had a synergistic effect on the hepatic E2 down-regulation of ER beta b, but apparently blocked the ER alpha up-regulation by E2. Conclusion These results demonstrate that ICI has agonistic effects on several typical estrogenic responses in fish, but its actions are tissue-specific. The mechanisms for the ICI agonistic activity are still unknown; although the ICI induced up-regulation of ER alpha mRNA could be one of the factors contributing to the cellular response.